Military operations research quantitative decision making - Jaiswal, N. K. (International series in operations research & management science, 1997)
This is a systematic, state-of-the-art treatment of military operations research (MOR). It examines issues that relate to both tactical and strategic levels. Several examples have been solved in each chapter to illustrate the application of the techniques of MOR to military systems.